An Exploratory Study of the Potential Effects of Vision Training on Concussion Incidence in Football. - Clark, Joseph F.; Graman, Pat; Ellis, James K.; Mangine, Robert E.; Rauch, Joseph T.; Bixenmann, Ben; Hasselfeld, Kimberly A.; Divine, Jon G.; Colosimo, Angelo J.; Myer, Gregory D. (Optometry & Visual Performance, 2015)
Background: Vision training has become a component of sports enhancement training; however, quantifiable and validated improvement in visual performance has not been clearly demonstrated. In addition, there is minimal literature related to the effects of vision training on sports performance and injury risk reduction. The purpose of the current investigation was to determine the effects of vision training on peripheral vision and concussion incidence. Methods: Vision training was initiated among the University of Cincinnati football team at the beginning of the 2010 season and continued for four years (2010 to 2013). The sports vision enhancement was conducted during the two weeks of preseason camp. Typical vision training consisted of Dynavision D2 light board training, Nike strobe glasses, and tracking drills. Nike Strobe glasses and tracking drills were done with pairs of pitch-and-catch drills using footballs and tennis balls, with instructions to vary arc, speed, and trajectory. For skilled players, "high ball" drills were the focus, whereas for linemen, bounce passes and low pitch drills were stressed. Reaction time data was recorded for each athlete during every Dynavision D2 training session. We monitored the incidence of concussion during the four consecutive seasons of vision training, as well as the previous four consecutive seasons, and compared incidence of concussions (2006 to 2009 referent seasons v. 2010 to 2013 vision training seasons). Results: During the 2006-2013 pre- and regular football seasons, there were 41 sustained concussion events reported. The overall concussion incidence rate for the entire cohort was 5.1 cases per 100 player seasons. When the data were evaluated relative to vision trained versus referent untrained player seasons, a statistically significant lower rate of concussion was noted in player season in the vision training cohort (1.4 concussions per 100 player seasons) compared to players who did not receive the vision training (9.2 concussions per 100 player seasons; p<0.001). The decrease in injury frequency in competitive seasons with vision training was also associated with a concomitant decrease in missed play time. Discussion: The current data indicates an association of a decreased incidence of concussion among football players during the competitive seasons where vision training was performed as part of the preseason training. We suggest that better field awareness gained from vision training may assist in preparatory awareness to avoid concussioncausing injuries. Future large scale clinical trials are warranted to confirm the effects noted in this preliminary report.